2017
DOI: 10.1002/jsfa.8193
|View full text |Cite
|
Sign up to set email alerts
|

Production of d‐allulose from d‐glucose by Escherichia coli transformant cells co‐expressing d‐glucose isomerase and d‐psicose 3‐epimerase genes

Abstract: A recombinant co-expression strain that catalysed the bioconversion of d-allulose from d-glucose in a one-step process was created and characterised. When adding 500 g L d-glucose as a substrate, 204.3 g L d-fructose and 89.1 g L d-allulose were produced. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Cascade catalysis is considered as a very attractive approach compared with traditional step-by-step synthesis. This strategy is often used to produce rare sugars from inexpensive materials, such as sucrose, Jerusalem artichoke, inulin, and fruit/vegetable residues ( Figure 3 ; Wagner et al, 2015 ; Song et al, 2016 , 2017 ; Zhang et al, 2017 ; Yang et al, 2019 ; Li et al, 2020a ). D-Allulose has been efficiently synthesized from sucrose using purified recombinant invertase, D-xylose isomerase, and DTEase.…”
Section: Biological Production Of D-allulosementioning
confidence: 99%
See 1 more Smart Citation
“…Cascade catalysis is considered as a very attractive approach compared with traditional step-by-step synthesis. This strategy is often used to produce rare sugars from inexpensive materials, such as sucrose, Jerusalem artichoke, inulin, and fruit/vegetable residues ( Figure 3 ; Wagner et al, 2015 ; Song et al, 2016 , 2017 ; Zhang et al, 2017 ; Yang et al, 2019 ; Li et al, 2020a ). D-Allulose has been efficiently synthesized from sucrose using purified recombinant invertase, D-xylose isomerase, and DTEase.…”
Section: Biological Production Of D-allulosementioning
confidence: 99%
“…Engineered Escherichia coli is one of the most commonly used organisms for the production of D-allulose because of its clear background, fast growth rates, simple culture, and stable genetics. DAEase and D-glucose isomerase (GIase) from Acidothermus cellulolyticus were coexpressed to produce D-allulose from D-glucose ( Zhang et al, 2017 ). Similarly, DAEase and xylose isomerase (XI) were coexpressed to produce D-allulose with D-glucose as the substrate ( Chen et al, 2017 ).…”
Section: Biological Production Of D-allulosementioning
confidence: 99%
“…In addition, the two enzymes are situated close together in space, creating a microenvironment rich in Dfructose for DPE, and reducing the diffusion time of Dfructose to DPE (Men et al, 2014). Zhang et al (2017) developed another recombinant E. coli strain that co-expressed both glucose isomerase and DPE. When 500 g/L glucose was used as the substrate, 204.3 g/L of D-fructose and 89.1 g/L of D-allulose could be obtained from D-glucose isomerase and DPE, respectively.…”
Section: Dual Enzyme Strategiesmentioning
confidence: 99%
“…It has been demonstrated that immobilization of whole cells via different polymers, agar, carrageenan, alginate gels, polyvinyl alcohol, or polyurethane foam, can effectively increase whole-cell stability and reusability [21][22][23][24][25]. Immobilized whole-cell systems can minimize damage from external environmental factors and maintain their stability under high-temperature conditions [26], immobilization technology was used for biocatalyst d-psicose production.…”
Section: Introductionmentioning
confidence: 99%